Recurrent Preterm Birth Reduction by 17-Hydroxyprogesterone Caproate in Dichorionic/Diamniotic Twin Gestation - Megli, Christina; Combs, C. Andrew; Venkataramanan, Raman; Lemon, Lara; Caritis, Steve N. (American Journal of Perinatology, 2020)
Objective The study aimed to evaluate the impact of 17-hydroxyprogesterone caproate (17-OHPC) on recurrent preterm birth (PTB) in women with a prior PTB and a current dichorionic/diamniotic twin gestation.Study Design We combined individual patient-level data from two prospective randomized placebo-controlled trials of prophylactic 17-OHPC in twin gestation and compared the rates of recurrent spontaneous PTB in those women with a prior singleton PTB randomized to placebo or 17-OHPC (250 mg weekly).Results Only 7.4% of women with dichorionic/diamniotic twin gestation experienced a prior PTB. Among these 66 women, spontaneous delivery prior to 34 weeks occurred significantly less often (p = 0.03) in those randomized to 17-OHPC (20.6%) than in those randomized to placebo (46.9%). However, mean gestational length was not significantly different, and there was no statistically significant difference in composite neonatal outcome.Conclusion 17-OHPC may be beneficial to women with a prior PTB and a current dichorionic/diamniotic twin gestation. These findings along with those reported by the Maternal Fetal Medicine Units Network in singletons suggest a common mechanism of action and a specific target population, those with a prior PTB, that may benefit from 17-OHPC treatment. A large prospective trial is needed to validate these findings.Key Points
Keywords: twins; prior preterm birth; 17-hydroxyprogesterone caproate